2019
DOI: 10.1007/s13592-019-00724-6
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of coumaphos in beeswax after treatment of honeybee colonies with CheckMite® against the parasitical mite Varroa destructor

Abstract: We studied the distribution of coumaphos in beeswax after a single application of CheckMite® to 15 bee colonies in the fall according to the manufacturer's instruction. Immediately after the treatment, residue levels were especially elevated in the wax that came into contact with the CheckMite® strips. During the following spring season, coumaphos levels ranged from 36 to 159 mg/kg in the wax of the brood frames next to the CheckMite® strips, and residue levels were about 10 times lower in the wax of frames th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…The coumaphos concentration in Apulia organic honey ranged between 0.322 and 2.132 ng/g, which is a result consistent with those reported for Calabria and Trentino organic honey [ 13 ]. Although this result could be considered surprising, since the use of allopathic chemically-synthetized medicinal products for preventive bee treatments is prohibited for organic system production, many studies have reported that coumaphos is persistent in wax and can migrate to other bee products, such as honey, in different proportions [ 17 , 18 ]. Moreover, coumaphos is a compound that can also resist the melting temperature of wax, so it is able to accumulate for years, as it is a common beekeeping practice to recycle wax almost continuously in the form of the foundations on which bees construct a complete comb [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coumaphos concentration in Apulia organic honey ranged between 0.322 and 2.132 ng/g, which is a result consistent with those reported for Calabria and Trentino organic honey [ 13 ]. Although this result could be considered surprising, since the use of allopathic chemically-synthetized medicinal products for preventive bee treatments is prohibited for organic system production, many studies have reported that coumaphos is persistent in wax and can migrate to other bee products, such as honey, in different proportions [ 17 , 18 ]. Moreover, coumaphos is a compound that can also resist the melting temperature of wax, so it is able to accumulate for years, as it is a common beekeeping practice to recycle wax almost continuously in the form of the foundations on which bees construct a complete comb [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Organophosphates can induce acute poisoning via food consumption due to their acetylcholinesterase inhibition activity, representing a life-threatening concern [ 15 , 16 ]. This class of pesticides, widely used in agriculture to protect against crop-eating insects and to control Varroa destructor , represents a consistent contamination source [ 17 , 18 ]. Due to the common beekeeping practice of recycling old wax combs, OP residues accumulate over time, increasing the potential contamination of the following cycle [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the survey was conducted on a voluntary basis, it is possible that it does not entirely reflect the average of the treatments used in Switzerland. However, we have previously shown that a single application for CheckMite+® (2.72 g of coumaphos in two strips) can lead to levels ranging from 36 to 159 mg·kg −1 in the wax of the brood frames next to the strips 7 months after the end of the treatment 34,35 . Hence, residue levels in the common beeswax may substantially increase if only a few beekeepers use products with a high dosage.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic acaricides could then provide good results for preventing colony losses [75]. Growing data have been published on acaricide residues in honey bee colony matrices, particularly in wax, which have the chemical properties to store the used lipophilic acaricides at concentrations that could even be toxic to the bees [78,87,88].…”
Section: Chemical Controlmentioning
confidence: 99%